Scientific Opinion on the risk posed by Shiga toxin‐producing Escherichia coli (STEC) and other pathogenic bacteria in seeds and sprouted seeds - EFSA Panel on Biological Hazards (BIOHAZ) (Wiley, 2011)
Abstract Sprouted seeds are young seedlings obtained from the germination of seeds. They are ready‐to‐eat foods which have caused large outbreaks. The bacterial pathogens most frequently associated with illness due to contaminated sprouted seeds are Salmonella and to a lesser extent STEC. Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus and Yersinia enterocolitica have also been transmitted by sprouted seeds, albeit very rarely. Dry seed contaminated with bacterial pathogens has been identified as the most likely initial source of sprout‐associated outbreaks; although other routes of contamination (e.g. during production due to poor practices) may also occur. In some outbreaks, contamination of seeds with as low as 4 Salmonella per kg was sufficient for the sprouts to cause disease. Seeds purchased by sprouts producers are usually not grown specifically for this purpose. They may be contaminated during production, harvest, storage and transport, and there may be difficulties in traceability of seeds from production to sprouting. Bacterial pathogens on seeds may survive for long periods during seed storage. There is so far no guarantee of a bactericidal step which is able to control contamination of seeds with bacterial foodborne pathogens acquired prior to germination. Due to the high humidity and the favourable temperature during sprouting, bacterial pathogens present on dry seeds can multiply on the sprouts. Contamination with pathogenic bacteria must be minimized by identification of seed crops intended for sprouted seeds production before planting, and application of GAP, GHP, GMP, HACCP principles at all steps of the production chain. The relevance of decontamination treatments of seeds and of microbiological criteria is also discussed.